O-184 Maternally inherited differences in mitochondrial DNA genotype between ART and spontaneously conceived individuals associate with low birthweight. (6th August 2021) - Mertens, J; Belva, F; Van Montfoort, A; Zambelli, F; Seneca, S; Couvreu de Deckersberg, E; Bonduelle, M; Tournaye, H; Stouffs, K; Barbé, K; Smeets, H; Van de Velde, H; et al.
Abstract: Study question: Can mitochondrial DNA (mtDNA) variants explain the differences in birthweight between ART and spontaneously conceived (SC) individuals and how do they originate? Summary answer: Children born after ART carry more frequently a different mtDNA variant composition, both maternally inherited and de novo, which are predictive of their birthweight percentile. What is known already: Children born after ART show an increased risk of lower birthweight and of developing a mild abnormal cardio-metabolic profile later in life. Variation in the mtDNA associates with overall health in the general population, including cardio-metabolic fitness, and can result in changes in mitochondrial function. We hypothesized that mitochondrial DNA variants could explain the differences in birthweight between ART and SC individuals and that these differences may result from maternal transmission and/or from the ovarian stimulation (OS) used in ART. Study design, size, duration: We deep-sequenced the mtDNA of 472 individuals of who 283 ART and 189 SC, 182 mother-child pairs and 113 single oocytes from both natural menstrual cycles and OS cycles. The mtDNA was compared between groups and Fisher linear discriminant analysis was used as predictive model for the birthweight percentile. Participants/materials, setting, methods: Mitochondrial DNA was enriched by long-range PCR and subsequently sequenced on an Illumina platform. mtDNA server and MuTect were used for variant calling for variants with a load higher than 1.5%, versus the reference NC_012920.1. An orthogonally rotated factor analysis was used to reduce the dimensionality of the studied dependent variables in the complex data of the heteroplasmic variants. Main results and the role of chance: ART individuals carried more frequently haplogroup U4 (p = 0.004) and component analysis indicated that they carry a different mtDNA heteroplasmic variant composition than SC individuals (p = 0.01), driven by non-synonymous protein-coding and rRNA-coding variants. These differences were also predictive of the risk of a lower birthweight percentile, especially for the SC children, together with the absence of haplogroup T, the presence of homoplasmic tRNA-variants, pregnancy-induced hypertension and the embryo culture medium used. The differences in heteroplasmic variation observed in the ART children resulted from both maternal transmission (p = 0.03) and de novo mutagenesis (p = 0.02). Mothers of ART children showed a similar mtDNA genotype as their children and differed in the same variant composition when compared to the mothers of SC children (p = 0.03). Furthermore, the comparison of oocytes from the same donors retrieved in natural menstrual cycles and after one OS cycle showed that OS does not increase de novo mutagenesis. Additionally, clinical parameters such as the total dosage of FSH units, the number of oocytes retrieved, and maternal age did not show any correlation with the differences observed in ART individuals. Limitations, reasons for caution: This study is observational with no functional tests being performed. Wider implications of the findings: We demonstrate an association between a lower birthweight percentile and a mtDNA variant composition which is more frequently carried by ART children. These non-disease associated mtDNA variants could cause a suboptimal mitochondrial function affecting the birthweight. Long-term health consequences of these differences remain to be further elucidated. Trial registration number: Not applicable